2005
DOI: 10.1002/adma.200501350
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phase Purity in Organic Semiconductors by Lattice‐Phonon Confocal Raman Mapping: Application to Pentacene

Abstract: propagation geometry, we have performed the retrieval [7,9] of the effective magnetic permeability l and the effective electric permittivity e on the basis of calculated optical spectra. Generally, the shape of the retrieved spectra of e and l are similar to those, e.g., shown in Figure 4 of our recent publication. [7] Thus, the retrieved spectra are not shown here. For the SRR parameters of the first row of Figure 4 we find a resonance in l with l < 0 around a wavelength of 2.4 lm. For the SRR parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
85
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 28 publications
1
85
0
2
Order By: Relevance
“…X-ray powder diffraction and Raman scattering allow identification of the two polymorphic forms, [16] and pressure experiments have revealed that the 14.5 Å polymorph irreversibly transforms into the 14.1 Å polymorph at elevated pressures. [10,17,18] Energy-minimization using quasi-Monte-Carlo sampling have been employed to study the stability of polymorphs of pentacene: the two observed phases (14.1 Å and 14.5 Å) represent the deepest energy minima, [19] that is, the most stable forms of pentacene. Despite interest in the use of pentacene as an organicsemiconductor material, and the continuing efforts to characterize the various crystal forms, doubts have remained until now about both the existence of a high-temperature polymorph of pentacene and its structure and thermal-expansion properties.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray powder diffraction and Raman scattering allow identification of the two polymorphic forms, [16] and pressure experiments have revealed that the 14.5 Å polymorph irreversibly transforms into the 14.1 Å polymorph at elevated pressures. [10,17,18] Energy-minimization using quasi-Monte-Carlo sampling have been employed to study the stability of polymorphs of pentacene: the two observed phases (14.1 Å and 14.5 Å) represent the deepest energy minima, [19] that is, the most stable forms of pentacene. Despite interest in the use of pentacene as an organicsemiconductor material, and the continuing efforts to characterize the various crystal forms, doubts have remained until now about both the existence of a high-temperature polymorph of pentacene and its structure and thermal-expansion properties.…”
mentioning
confidence: 99%
“…Upon cooling, this phase could be observed down to room temperature, indicating quenching of this high-temperature phase, consistent with previous observations of polymorphism in pentacene powders. [18] Our first attempts to use powder diffraction to obtain a crystal structure of the high-temperature phase were hampered by the fact that no single-phase powder pattern could be obtained, and the peak overlap between the two phases was substantial. Further experiments using single crystals heated to temperatures above 463 K eventually provided sufficient data for a singlecrystal structure determination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to optimize device performance, it is of course necessary to properly characterize the chemical and physical purity of the sample, as impurities and static or dynamic disorder have a decisive role in determining the carrier localization [3,4]. Pentacene is also the system on which the need of controlling the phase purity of the crystal has been first underlined, as different polymorphs may occur in the same crystallite [5]. The polymorphism in pentacene has indeed attracted many experimental and theoretical works [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…SiC ceramics have several kinds of crystal forms, and could be easily detected and distinguished in Raman spectra that provide a wide range of information about the chemical structures with very strong signal of frequency, intensity, and width [15][16][17], so that μ-RS has been used in detecting the composition changes of laser-ablated SiC surface [11,12]. Moreover, micro-Raman mapping technology, a spatially resolved technique, allows one to characterize the phase distribution of chemical structures in a specific region of material surface by 2D images [18][19][20], possibly an effective technique to study the laser ablation of SiC ceramics.…”
Section: Introductionmentioning
confidence: 99%